How doth the little busy bee: unexpected metabolism. Issue 1 (January 2015) - Barros, L. Felipe; Sierralta, Jimena; Weber, Bruno
Highlights Aggressive honey bees have lower activity of OXPHOS enzymes in the brain. A recent study shows that OXPHOS inhibition causes aggressive behavior in insects. Possible links between energy metabolism and behavior are discussed.